The battlefield at home: the meaning of homelessness from the female veteran’s perspective - Miller, Chiquita (Kansas State University, 2015)
Homelessness has become an enduring fixture of contemporary United States society. Female veterans face a host of unique challenges; females often carry the burden of serving in the armed forces, while balancing marriages, motherhood, and care giving responsibilities in their home lives. As the veterans return to their lives as civilians, the females who served in the military must deal with the possibility of sexual harassment, sexual assault, and rape while in the armed services. Female service members are twice as likely to have Post Traumatic Stress Disorder (PSTD) than their male service members and are three to four times more likely to become homeless. Understanding this view of homelessness from the female veteran’s perspective is limited due to small sample sizes in previous research efforts. However, with the increasing numbers of homeless female veterans it is imperative to understand the risk factors. A qualitative descriptive study was conducted using a modified framework for studying vulnerable populations. The study was designed to explore the meaning of homelessness from the female homeless veteran’s perspective. Second, risk factors were examined for homelessness and the services necessary for the female veteran to exit the homeless cycle. Third, the data were coded and analyzed to identify patterns and commonalities of multiple psycho social factors such as unstable family support, domestic violence, job loss, affordable housing options, substance abuse, mental and physical health issues. These factors were cited as the leading risk factors contributing to the homeless state of this sample of female veterans. The data collection consisted of ten homeless female veterans participating in a private, audio taped interview using a semi-structure interview tool. Resources listed as a necessity to end homelessness consisted of affordable housing, job security, earning a living wage income, transportation, remaining drug free, and being awarded disability. The pathway to homelessness varied for each participant, but they all demonstrated a tremendous amount of resiliency.
Keywords: Female; Homeless; Veteran; Military; Risk factors; Post traumatic stress disorders; Individual & Family Studies (0628); Military Studies (0750); Social Research (0344)